2019
DOI: 10.5546/aap.2019.eng.e347
|View full text |Cite
|
Sign up to set email alerts
|

Reference percentiles for mid-upper arm circumference, upper arm muscle and fat areas in the Argentine child and adolescent population (4-14 years old)

Abstract: Introduction: Mid-upper arm circumference (MUAC) is widely recognized as an adequate indicator of nutritional status. Objective: To estimate the reference percentiles for MUAC, upper arm muscle area (UAMA), and upper arm fat area (UAFA) in the Argentine child and adolescent population using the LMS method (lambda, mu, sigma) Materials and methods: The sample was made up of schoolchildren aged 4.0-13.9 years living in Jujuy, Catamarca, Misiones, Buenos Aires, Mendoza, and Chubut. MUAC and tricipital skinfold an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 12 publications
0
1
0
Order By: Relevance
“…Results for UAFA indicate significant difference from age 4.5 years and the sex difference was consistently in favour of girls. Our findings on UAMA and UAFA were in congruent to that of Oyhenart [14]. This is due to sexual dimorphism that exists in body composition with girls having relatively more fat mass and boys more muscle.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…Results for UAFA indicate significant difference from age 4.5 years and the sex difference was consistently in favour of girls. Our findings on UAMA and UAFA were in congruent to that of Oyhenart [14]. This is due to sexual dimorphism that exists in body composition with girls having relatively more fat mass and boys more muscle.…”
Section: Discussionsupporting
confidence: 81%
“…Recently, analysis of MUAC body composition and its derivative outcome indicators; upper arm muscle area (UAMA) and upper arm fat area (UAFA) references have been published [14] among Argentinian children and adolescents, similar to the one earlier published by Frisancho (2008) and Addo et al (2017) of children and adolescents in the US [15,16]. In Nigeria, to our knowledge, no reference values of MUAC, UAMA and UAFA of children and adolescents have been published, thereby underscoring the huge gap in data in the largest black African countries in the world.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, a significant difference according to sex and age in undernutrition was observed in some studies (24)(25)(26). Hence, no universal agreement on the MUAC cut-off point to screen malnutrition among children and adolescents (27,28). Therefore, adopting local references of MUAC for epidemiological and anthropological studies is recommended (29).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, adopting local references of MUAC for epidemiological and anthropological studies is recommended (29). Several previous studies reported that MUAC could be an alternative tool to detect underweight/thinness among adolescents (8,13,21,(27)(28)(29). MAUC is useful in different clinical situations, e.g., in cases of adolescents who have edema (7), chronic disorders and growth failure (9,30,31), cerebral palsy (11) severe learning disabilities (32), and anorexia nervosa (33,34).…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, there is no agreement as to which side of the body should be assessed for anthropometric measurements (Madden & Smith, 2016;Moreno et al, 2002), and it is important to have reference values that reflect population variability, whenever possible, especially for nutritional status assessment (Oyhenart et al, 2019).…”
Section: Introductionmentioning
confidence: 99%